2019
DOI: 10.1503/cmaj.190111
|View full text |Cite
|
Sign up to set email alerts
|

Health Services

Abstract: S troke is the third leading cause of death in high-income countries, and accounts for substantial morbidity in those who survive. 1 Ischemic stroke is primarily due to a thrombotic or embolic event, and emboli frequently originate in the heart. 2 Transthoracic echocardiography can sometimes diagnose cardiac sources of embolism, such as atrial or ventricular thrombus, 3-5 and these generally require anticoagulation. Transthoracic echocardiography can also identify other causes of stroke that may require interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Previous studies reported clinically relevant findings on TTE in 3-37% of stroke patients, though nearly all studies report rates below 20%. [1][2][3][4][5][6][7] This variability is most likely explained by evolving definitions of clinically relevant findings and subsequent management based on current practices. For example, we chose to exclude PFO or left atrial enlargement as they do not immediately change management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported clinically relevant findings on TTE in 3-37% of stroke patients, though nearly all studies report rates below 20%. [1][2][3][4][5][6][7] This variability is most likely explained by evolving definitions of clinically relevant findings and subsequent management based on current practices. For example, we chose to exclude PFO or left atrial enlargement as they do not immediately change management.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent Canadian study reported that median length of hospital stay for stroke patients was 3 days longer for patients receiving echocardiography, suggesting that prolonging inpatient admission to expedite TTE is not unique to our center. 7 There is limited data regarding the cost-effectiveness of TTE in secondary stroke prevention. Two prior American studies used computer modeling to complete a costeffectiveness analysis of echocardiography after first ischemic stroke, and both found that TTE alone or in combination with other strategies was not cost-effective, though one found TEE to be cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of TEE in the cohort in the present study was low, occurring in just 1 out of 10 stroke patients. In a multicenter cohort study of nearly 2.000 patients with ischemic stroke or TIA, 68% had an echocardiogram (most often a transthoracic), and the results were normal 86% of the time, whereas the 2 most common clinically actionable indings for secondary stroke prevention were cardiac thrombus and PFO [33]. The wide range of estimates for how often "clinically relevant" indings are detected on echocardiogram for patients with an ischemic stroke is partially related to changing criteria for what is considered clinically relevant, e.g., anticoagulation is no longer recommended in clinical practice guidelines for dilated cardiomyopathy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Transözofageal ekokardiyografi (TEE) kardiyoembolik inmede intrakardiyak ve sol atriyal trombüsü dışlamakta daha duyarlıdır. Ancak transtorasik ekokardiyografi (TTE) daha kolay ulaşılabilen ve uygulanabilen bir inceleme yöntemidir [5].…”
Section: Introductionunclassified